SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SANTRI TELADAN PONDOK PESANTREN AL-MUHAJIRIN MENGGUNAKAN METODE AHP BERBASIS WEB - Enrico Yoga Kusuma; Tanhella Zein Vitadiar; Ginanjar Setyo Permadi; Hery Kristianto (Fakultas Teknologi Informasi, 2025)
Determining the ranking of exemplary students can often be challenging due to the lack of systems toassist in decision-making. One applicable model is the Decision Support System (DSS). DSS isdesigned to enhance decision-makers' capabilities by providing necessary information and analysisbased on predefined criteria set by Pondok Pesantren. DSS aims not to replace human judgment butto aid in complex decision-making processes. In the context of Pondok Pesantren Al-Muhajirin,selecting exemplary students is often difficult due to the absence of objective methods to swiftlyassess eligibility based on available data. This research proposes using a web-based DecisionSupport System employing the Analytical Hierarchy Process (AHP). AHP is a method that helps organize and analyze various relevant criteria during decision-making processes, thereby enabling a more effective selection of students deserving the title of exemplary student and scholarships. The findings of this study indicate that implementing a Decision Support System using AHP successfully yields final outcomes usable by decision-makers at Pondok Pesantren. Thus, this system not only enhances objectivity in the selection process but also accelerates and optimizes decision-making based on available data. Keywords : Exemplary Student, Analytical Hierarchy Process (AHP), Decision Support System